Differing Perceptions of Attorney Fees in Bankruptcy Cases - Theodore Eisenberg (Washington University Law Quarterly, 1994)
Part I describes the data. Part II shows that both judges and lawyers view the fee system through a self-serving lens. Each group tends to overstate the merits of its professional performance compared to the other group's perception of that performance. Part III explores interstate differences as a source of differing perceptions. It finds that judge and lawyer perceptions of the same reality can be as important as the real variation across states.
Keywords: Bankruptcy; Lawyers – Fees; Bankruptcy reorganization